A New Harmonic Compensation Based Modified Field Oriented Control of Permanent Magnet BLDC Motor with Reduced Torque Pulsation - Roy I.; Chaudhary K.; Jain A.K. (My University, 2025)
This paper presents a novel current harmonic compensation based modified Field-Oriented-Control (FOC) for permanent magnet BLDC motor to mitigate torque ripples. A brief analysis of conventional vector control of PMBLDC motor is presented. The proposed FOC for BLDC motor is based on harmonic compensation of stator current. To implement the current harmonic compensation the harmonic analysis of back emf in rotor reference frame has been carried out. To track harmonic components a Proportional-Resonant (P-R) based current controller is designed considering motor drive parameters and desired dynamic performance. The proposed method rejects all the torque ripples without compromising the dynamic response of motor drive. Validation of this modified control is validated using MATLAB/SIMULINK environment and experimental setup both. © 2023 IEEE.